Multitemporal Analysis of the Water Quality Index (WQI) in Surface Currents in the Upper Basin of the Bogotá River (Colombia) - Sanabria Súarez, Andrea Cecilia; Montenegro Marín, Carlos; Castro Fernández, Mario Fernando; Díaz Casallas, Daissy Milena (Ingeniería Solidaria, 2017)
Introduction: This article presents the variations in water quality in the upper basin of the Bogotá River by interpreting the results obtained from the semiannual monitoring conducted by the Cundinamarca environmental authority (Corporación Autónoma Regional - car) during 2008-2015. These results correspond to the research project Economic, social and institutional variables of greater influence over second generation indicators related to the water resource and its management, carried out by the research group Neotic of the School of Engineering, Universidad Cooperativa de Colombia, Bogotá, during 2016. Method: Based on the information provided by car, the water quality index (wqi) established by the Institute of Hydrology, Meteorology and Environmental Studies (ideam) for Colombia was calculated. Results: The excessive use of agrochemicals in the upper basin of the Bogotá River has repercussions on it, since water quality already shows deterioration from this place. Anthropic factors are the main cause of pollution and environmental deterioration due to agroindustrial operations carried out around its waters. Conclusions: Although municipal mayors are aware of the problems of the Bogotá River and include mechanisms to address them in their municipal development plans, the results obtained demonstrate the need to formulate new environmental strategies or reformulate existing ones for the care and protection of this resource.